The impact of perceived interactivity on purchase intention in interactive video: a CAB-based chain mediation model of empathy, immersion, and arousal - Li, Yichen; Sun, Meijui (Frontiers in Communication, 2025)
IntroductionWith the rising popularity of interactive video content in China, understanding how interactivity influences consumer behavior has become increasingly important.MethodsThis study employs the Cognitive-Affective-Behavioral (CAB) model to construct a chain mediation framework, wherein perceived interactivity influences purchase intention through affective (empathy and immersion) and psychological (arousal) pathways. A total of 429 valid survey responses were collected and analyzed using structural equation modeling.ResultsThe findings indicate that perceived interactivity significantly enhances both empathy and immersion. These affective responses, in turn, increase arousal, which subsequently leads to stronger purchase intentions.DiscussionThis study extends the applicability of the CAB model to the domain of interactive media and provides actionable implications for enhancing content and interface design in interactive video platforms.